Kontribusi Nilai Islam Dalam Ranah Bisnis Dan Pemasaran - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Ethics are all general norms or "rules" that must be considered in doing business which are the source of noble values ​​and good deeds. In Indonesia, it highly upholds moral and ethical values ​​in every behavior of daily life. Of course this makes the marketing (marketing) also must obey whatever has been arranged to be in line with the socio-cultural values ​​of the community. If it is related to business, then the norm aspect is about what is appropriate or inappropriate for someone when running a business in order to get profit. Business has several systems that consist of input inventory, processes to activities that produce output. The series of activities include production, distribution, capital, and marketing. All of these things must be carried out in accordance with the applicable syari’ah rules, so that in running its business, a Muslim is not only oriented in the business of the world, but oriented horizontally and vertically. So, Islamic ethics in the fields of business and marketing is very necessary, especially Islamic ethics for Muslim entrepreneurs.